Garfield by the pound - Davis, Jim, 1945 July 28- (New York : Ballantine, 1992)
Collection of black-and-white cartoon strips featuring the perpetually hungry cat Garfield and his friends.
"His 22nd book"--Cover.
4.0
5-8
Keywords: Cartoons and comics; Cats -- Fiction; Garfield (Fictitious character) -- Fiction; Cats -- Fiction; Comic books, strips, etc; Garfield (Fictional character) -- Fiction